Physiological acclimation dampens initial effects of elevated temperature and atmospheric CO2 concentration in mature boreal Norway spruce. (11th December 2017) - Lamba, Shubhangi; Hall, Marianne; Räntfors, Mats; Chaudhary, Nitin; Linder, Sune; Way, Danielle; Uddling, Johan; Wallin, Göran
Abstract: Physiological processes of terrestrial plants regulate the land–atmosphere exchange of carbon, water, and energy, yet few studies have explored the acclimation responses of mature boreal conifer trees to climate change. Here we explored the acclimation responses of photosynthesis, respiration, and stomatal conductance to elevated temperature and/or CO2 concentration ([CO2 ]) in a 3‐year field experiment with mature boreal Norway spruce. We found that elevated [CO2 ] decreased photosynthetic carboxylation capacity (−23% at 25 °C) and increased shoot respiration (+64% at 15 °C), while warming had no significant effects. Shoot respiration, but not photosynthetic capacity, exhibited seasonal acclimation. Stomatal conductance at light saturation and a vapour pressure deficit of 1 kPa was unaffected by elevated [CO2 ] but significantly decreased (−27%) by warming, and the ratio of intercellular to ambient [CO2 ] was enhanced (+17%) by elevated [CO2 ] and decreased (−12%) by warming. Many of these responses differ from those typically observed in temperate tree species. Our results show that long‐term physiological acclimation dampens the initial stimulation of plant net carbon assimilation to elevated [CO2 ], and of plant water use to warming. Models that do not account for these responses may thus overestimate the impacts of climate change on future boreal vegetation–atmosphere interactions. Abstract : Physiological processes of terrestrial plants regulate the land–atmosphere exchange of carbon, water, and energy, yet few studies have explored the acclimation responses of mature boreal conifer trees to climate change. Here we explored the acclimation responses of photosynthesis, respiration, and stomatal conductance to elevated temperature and/or CO2 concentration ([CO2 ]) in a 3‐year field experiment with mature boreal Norway spruce. We found significant acclimation responses of all three physiological variables, which often differed from responses typically observed in temperate tree species and always acted to dampen the initial effects of elevated [CO2 ] and warming on tree carbon assimilation and water use. Our results highlight the importance of models accounting for these long‐term acclimation responses, or otherwise they risk to overestimate the impacts of climate change on future boreal vegetation–atmosphere interactions.